A triple oxygen isotope perspective on the origin, evolution, and diagenetic alteration of carbonatites. (15th April 2021) - Fosu, Benjamin R.; Ghosh, Prosenjit; Weisenberger, Tobias B.; Spürgin, Simon; Viladkar, Shrinivas G.
Abstract: Carbonatites are unique magmatic rocks that are essentially composed of carbonates, and they usually host a diverse suite of minor and accessory minerals. To provide additional insights on their petrogenesis, triple oxygen isotope analyses were carried out on carbonatites from sixteen localities worldwide in order to assess the behaviour of oxygen isotopes (mass-dependent fractionation) during their formation. The study evaluates the mineralogical differences, i.e., calcite, dolomite, ankerite, and Na-carbonates, and the mode of emplacement (intrusive or extrusive) in the mantle-derived carbonatites to further constrain the triple oxygen isotopic composition (Δ′ 17 O) of the upper mantle. Δ′ 17 O values in the intrusive calcite carbonatites vary between −0.003 to −0.088‰ (n = 20) and −0.024 to −0.085‰ (n = 5) in the dolomite varieties. We surmise that the magnitude of isotopic fractionation in the different carbonate phases during their formation is similar and thus, the observed variations are independent of mineralogy and may be related to alteration in the rocks. Taking the samples that classify as primary igneous carbonatites altogether, the average Δ′ 17 O value of the mantle is estimated as −0.047 ± 0.027‰ (1SD, n = 18) which overlaps those of other mantle rocks, minerals and xenoliths, indicating that the mantle has a relatively homogenous oxygen isotope composition. Two ankerite carbonatites have identical Δ′ 17 O values as calcite but a few samples, together with pyroclastic tuffs have significantly lower Δ′ 17 O values (−0.108 to −0.161‰). This deviation from mantle Δ′ 17 O signature suggests diagenetic alteration (dissolution and recrystallisation) and mixing of carbonate sources (juvenile and secondary carbonates) which is consistent with the high δ 18 O and clumped isotope (Δ47 ) values recorded in the pyroclastic and ankeritic rocks. In summary, diagenetic alteration driven by fluid-rock interaction at low temperatures, sub-solidus re-equilibration with magmatic waters, and the incorporation of secondary carbonates altogether facilitate the alteration of original isotopic compositions of carbonatites, obliterating their primary mantle signatures.